Climate Change Mitigation Through Corporate Social Responsibility (CSR) Program: Community-Based Organic Waste Management - Fabian Panji Ayodya; Jauhari Ali; Lifania Riski Nugrahani; Rhizky Alexander (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
Climate change is a problem that must be taken seriously. Climate change is also caused by the presence of waste that continues to grow. The majority of waste sources in Indonesia come from household waste. Waste management can be carried out directly at the source by processing it through groups in the community, as is done by TPST Masa Sejati and PETRATONIK. This study uses a qualitative descriptive method to explain community-based organic waste management which has an impact on climate change mitigation at PT Kilang Pertamina Internasional RU V Balikpapan. Efforts to handle waste are carried out by processing organic waste into compost using the Takakura method and bioconversion of waste through BSF. Besides being useful for reducing waste, this handling activity also provides added value to the community's income. The results of this study show that the CSR program carried out by PT Pertamina Internasional RU V Balikpapan Refinery enables the community to process organic waste in their environment (the source) into something of economic value and has implications for reducing methane gas, which is one of the greenhouse gases that is released into the atmosphere. This CSR program is able to reduce 3.3% of methane gas produced by total waste in Balikpapan City.